Paraguay : First Review Under the Stand-By Arrangement; Staff Report; Staff Supplement; and Press Release on the Executive Board Consideration. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Improvements in macroeconomic conditions are encouraging, and the current macroeconomic framework for 2006 and 2007 remains valid in Paraguay. The strong fiscal performance has applied also to the rest of the public sector. The authorities have submitted a budget proposal for 2007 that preserves fiscal discipline. Monetary policy will continue to be geared toward achieving the inflation target of 7 percent in 2006. Monetary policies will aim at a further reduction of inflation for 2007. Despite the recent strengthening of the balance of payments, external vulnerabilities remain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet